Toward a Conceptual Framework for the Knowledge Bank - Chioda, Laura; de la Torre, Augusto; Maloney, William F. (World Bank, Washington, DC, 2013)
This paper proposes some basic elements of a conceptual framework to help organize the thinking about policies that can strengthen the knowledge mission of the World Bank. It first argues that the Bank occupies a unique and prominent subset of the social and economic development "knowledge space" that ranges from abstract basic research to codified knowledge solutions. The fact that this niche centrally includes the provision of public good-intensive knowledge weakens organizational analogies between the Bank and private consulting firms. The range of products coupled with an increasing emphasis on just-in-time advisory services dictate the need for not more generalists, but rather an increased range and depth of very specific and high quality human capital. However, this increased specialization in turn creates the need for "hinge" actors who can communicate and operate well across different knowledge communities -- academics, policy makers, practitioners, etc. The necessary changes in human resource and incentive policies, in particular the critical development of better means of ensuring the quality of knowledge production, are an essential complement to any organizational restructuring.